Fragment hopping approach directed at design of HIV IN-LEDGF/p75 interaction inhibitors. (1st October 2013) - De Luca, Laura; Ferro, Stefania; Morreale, Francesca; Christ, Frauke; Debyser, Zeger; Chimirri, Alba; Gitto, Rosaria
Abstract : We recently identified a series of indole derivatives as active inhibitors of IN-LEDGF/p75 interaction through structure-based pharmacophore models generated from the crystal structure of dimeric catalytic core domain (CCD) of HIV-1 IN in complex with the LEDGF integrase binding domain (IBD). In this paper we used the fragment hopping approach to design small molecules able to prevent the IN-LEDGF/p75 interaction. By means of the proposed approach, we designed novel non-peptidyl compounds that mimic the biological function of some IBD residues and in particular the LEDGF hot spot residues Ile365 and Asp366. The biological results confirmed the importance of several structural requirements for the inhibitory effects of this class of compounds.